Needs Analysis on the Module Development for Working Sandwich Generation in public University in Malaysia - Rozita Jayus; Aqeel Khan; Adibah Abdul Latiff; Mastura Mahfar; Abdul Wahab Pathath (South Eastern European Journal of Public Health, 2024)
The number of caregivers of older people will increase to 60% by 2040 to maintain the current ratio of caregivers to older people, which in turn will impact on their mental health and career needs. This study provides the profile, characterisation and needs analysis of the samples, which were conducted using non-probability convenience sampling. This included 201 sandwich and non-sandwich generation working at a public university in relation to coping with caring responsibilities, workplace challenges, personal development and interest in specific programmes or support systems to strengthen and improve coping strategies, adaptability and resilience of employees in the workplace. Understanding these dynamics, improved the development of modules and services to better meet the specific needs of these groups. The aim of this study is to identify the need for stress coping strategies, career adaptability and career resilience and to analyse needs-based programmes for the working sandwich generation. The needs analysis shows that the development of modules must be taken into account when designing a career intervention modules. The research proposes a comprehensive intervention module for career guidance programs to aid sandwich generation in coping with stress, enhancing career adaptability and resilience.